Security penetration testing (The art of hacking series) (Pearson, 2018)
"This course is a complete guide to help you get up and running with your cybersecurity career. You will learn the key tenets and basics of ethical hacking and security penetration testing techniques. You will also explore professional networking and security topics, including an introduction to the world of white hat hacking, reconnaissance, Kali Linux, and exploitation. This course provides step-by-step real-life scenarios. You will see first hand how an ethical hacker performs initial reconnaissance of a victim and how to assess systems and network security controls security posture. With over 10 hours of training that includes live discussions, demos, whiteboard instruction and screencasts, Security Penetration Testing Live Lessons provides expert insights of the methodologies used to assess and compromise a network. It covers the legal aspects of ethical hacking and the associated risks. This course additionally reviews many different tools that can be used to penetrate a wired and wireless network and the systems within that network. The title also covers numerous types of attacks, along with security evasion and post exploitation techniques. You will additionally learn the art of social engineering, with special coverage of tools like the social engineering tool kit (SET), Metasploit, Maltego, and many more. After that you'll take a look at guidelines for how to write a penetration testing report, with instructions for how to plan and organize those reports examples of reports including several best practices."--Resource description page